All you want to know about hell : three Christian views of God's final solution to the problem of sin - Gregg, Steve, 1953- (Nashville : Thomas Nelson, 2013)
"It is an undeniable fact that the very concept of hell is shrouded in mystery. We know what books and movies tell us hell is like, but we're left with so many questions. Is hell simply a place where sinners are sent to suffer for their sins, or is it much, much more than that? All You Want to Know About Hell breaks down the three most popular views on hell and tells us what the Bible really says about this terrifying and mystifying place. From the "traditional" view of hell as a place of eternal torment to the early Christian view that hell is a place of suffering intended to purge sin and to bring about repentance, no other book gives such in-depth biblical insight into the truths about hell that are hidden in all the hype"--Amazon.com, viewed December 3, 2014.
Includes bibliographical references (pages 319-321).
Keywords: Hell -- Christianity